MENINGKATKAN PENYESUAIAN DIRI TERHADAP LINGKUNGAN SEKOLAH MELALUI LAYANAN BIMBINGAN KELOMPOK PADA SISWA KELAS X IA.1 SMAN 1 KINALI - Zulhardi, Zulhardi (Jurnal Manajemen Pendidikan, 2018)
Adjustment requires the ability of adolescents to live and socialize naturally to their environment, so that adolescents feel satisfied with themselves and also the environment. Adolescents with poor self-adjustment, their psychiatric life is characterized by emotional distress or anxiety that accompanies guilt, anxiety, dissatisfaction with what has been obtained, and complaints about what they experience. The purpose of this study is to determine whether the adjustment to the school environment in students of Class X IA.1 can be improved through group guidance services. This research is a classroom action research. The research procedures in this research include planning, action, observation and reflection. This study consists of two cycles with four meetings. Subek in the study were students of Class X IA.1 SMAN 1 Kinali amounted to 32 students. In the result of cycle 1, the average result obtained is 61,03% from all students have mean of positive adjustment in medium criterion with mean percentage equal to 60,96% and negative self adjustment from whole student show medium criterion with percentage equal to 61.46%. And after given treatment obtained by result of cycle 2 equal to 71,57% from all student have average of positive self adjustment in high criterion with mean percentage 72,28% and negative self adjustment from whole student showed medium criterion with percentage equal to 69, 58%. The results showed an increase in self-adjustment to the school environment on all students at 10.54% after treatment. The conclusion of this study is that there is an increase of self adjustment to school environment in the students of Class X IA.1 SMAN 1 Kinali after giving group guidance service.